THE DEVELOPMENT OF TECHNOLOGICAL METHODS OF LASER SURFACE TREATMENT OF HEAVILY LOADED PARTS WHEEL SET CARS - Sheliahin, V. D.; Khaskin, V. Yu.; Nikulin, O. T.; Bernatskyi, A. V.; Siora, O. V. (Science and Transport Progress, 2009)
Possibility of application of processes of laser superficial processing for restoration and increase of a resource of operation of shafts and rims of wheels of railway cars is investigated. The influence of critical parametres of process on depth of a zone of laser influence and their interrelation with the structure obtained and hardness is determineed.